Pharmacokinetic similarity of biologics: analysis using nonlinear mixed-effects modeling - Dubois, Anne (Nature Pub. Group, 2012)
Our objective was to show with two examples that a pharmacokinetic (PK) similarity analysis can be performed with nonlinear mixed effects models (NLMEM). We used two studies comparing different biosimilars: a three-way crossover trial on somatropin and a parallel group trial on epoetin alpha. For both datasets, NLMEM-based analysis was compared to non-compartmental analysis (NCA). As for NCA, we performed NLMEM-based equivalence Wald test on secondary parameters of the model: the area under the curve and the maximal concentration. Somatropin PK was described by a one-compartment model, epoetin alpha PK by a two-compartment model with linear and Michaelis-Menten elimination. For both studies, PK similarity was demonstrated by NCA and NLMEM. Both approaches led to similar results. Therefore, PK similarity data can be analyzed by both methods. NCA is an easier approach as it does not require data modelling but NLMEM leads to a better understanding of the underlying biological system.